Research progress of therapeutic vaccines for treating chronic hepatitis B - Jianqiang Li; Mengru Bao; Jun Ge; Sulin Ren; Tong Zhou; Fengchun Qi; Xiuying Pu; Jia Dou (Taylor & Francis Group, 2017)
Hepatitis B virus (HBV) is a member of Hepadnavirus family, which leads to chronic infection in around 5% of patients with a high risk of developing liver cirrhosis, liver failure, and hepatocellular carcinoma. Despite the availability of prophylactic vaccines against hepatitis B for over 3 decades, there are still more than 2 billion people have been infected and 240 million of them were chronic. Antiviral therapies currently used in the treatment of CHB (chronic hepatitis B) infection include peg-interferon, standard α-interferon and nucleos/tide analogs (NAs), but none of them can provide sustained control of viral replication. As an alternative strategy, therapeutic vaccines for CHB patients have been widely studied and showed some promising efficacies in dozens of preclinical and clinical trials. In this article, we review current research progress in several types of therapeutic vaccines for CHB treatment, including protein-based vaccines, DNA-based vaccines, live vector-based vaccines, peptide-based vaccines and cell-based therapies. These researches may provide some clues for developing new treatments in CHB infection.